(untitled) (Research, Society and Development, 2022)
Brazil has a diverse popular pharmacopoeia based on medicinal plants. Medicinal plants are used in the treatment of symptoms of advanced and incurable diseases, such as oncological palliative care, they can help in the preventive or curative treatment of these symptoms, providing greater comfort to these patients. The present work aims to collect data on medicinal plants with potential application in the treatment of symptoms resulting from cancer in oncological palliative care. An integrative review in the literature was carried out for references on medicinal plants and the crossing of these data with the most prevalent symptoms in oncological palliative care in reference books and databases. Seventeen plant species with potential use were identified. As tranquilizers we found lemongrass, lemon balm, passion fruit and “marcela”. Species with analgesic action, as adjuvants in the treatment of pain, in addition to the four species mentioned above, we found: rosemary, “boldo baiano”, ginger, aloe, “calendula” and “erva baleeira”. As wound healing plants, in addition to rosemary, aloe and “calendula”, we mention “aroeira”. Among the plant species effective in the treatment of digestive disorders, in addition to rosemary, lemon balm, ginger, marcela and “boldo baiano”, we can mention “boldo do chile”, “boldo brasileiro”, “cascara sagrada”, fennel, “espinheira-santa” and “cana-do-brejo”. The present work is an effort that aims to contribute to the population’s access, whether prescribers and/or patients, to offer credible information on medicinal plants with potential application in oncological palliative care. These plant species are native or easily cultivated in different Brazilain regions, which increases the probability of using these therapeutic resources.